Arene oxides in styrene metabolism, a new perspective in styrene toxicity? - Pantarotto, C.; Fanelli, R.; Bidoli, F.; Morazzoni, P.; Salmona, M.; Szczawinska, K. (Scandinavian Journal of Work, Environment & Health, 1978)
The metabolism of styrene was studied in the rat after intraperitoneal administration of the cold and the 14C-labeled compound. In addition to phenylethylene glycol, mandelic acid, benzoic acid and hippuric acid, phenolic metabolites, namely, 4-vinylphenol, p-hydroxymandelic acid, p-hydroxybenzoic acid, and p-hydroxyhippuric acid, were identified in the urine of the treated animals. These biotransformation products were characterized by mass spectrometry and by comparative thin layer chromatography with standard compounds. Results of covalent binding studies of 14C-phenylethylene glycol to rat liver microsomal proteins suggest that these phenolic compounds may be formed as a result of chemical rearrangements of unstable arene oxides, reactive intermediates possibly implicated in styrene toxicity.
Keywords: 4-vinylphenol; arene oxide; covalent binding; mass spectrometry; metabolism; p-hydroxybenzoic acid; p-hydroxyhippuric acid; p-hydroxymandelic acid; phenylethylene glycol; styrene; styrene metabolism; styrene toxicity; toxicity